2004
DOI: 10.1023/b:pres.0000017207.88257.d4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Uncovers Proteins Interacting Electrostatically with Thioredoxin in Chloroplasts

Abstract: The ability of thioredoxin f to form an electrostatic (non-covalent) complex, earlier found with fructose-1,6-bisphosphatase, was extended to include 27 previously unrecognized proteins functional in 11 processes of chloroplasts. The proteins were identified by combining thioredoxin f affinity chromatography with proteomic analysis using tandem mass spectrometry. The results provide evidence that an association with thioredoxin enables the interacting protein to achieve an optimal conformation, so as to facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 34 publications
2
55
0
1
Order By: Relevance
“…The Trx play an important role in redox regulation (activation and deactivation) of many biosynthetic and other activities in plastids (Balmer et al, 2004). The distribution of the different Trx between the M and BS chloroplasts has not been reported earlier, which is somewhat surprising given the central role of the Trx in regulating chloroplast function.…”
Section: Proteins Involved In Redox Regulationmentioning
confidence: 70%
“…The Trx play an important role in redox regulation (activation and deactivation) of many biosynthetic and other activities in plastids (Balmer et al, 2004). The distribution of the different Trx between the M and BS chloroplasts has not been reported earlier, which is somewhat surprising given the central role of the Trx in regulating chloroplast function.…”
Section: Proteins Involved In Redox Regulationmentioning
confidence: 70%
“…Yano et al used monobromobimane to label free thiols in proteins reduced by Trx that were resolved via two-dimensional gel electrophoresis and identified five Trx targets in peanut seeds (26). The Trx affinity technique was subsequently developed to identify Trx targets in diverse cell types, including spinach (27)(28)(29)(30)(31), Arabidopsis (32)(33)(34)(35), Escherichia coli (36,37), wheat seeds (38,39), Synechocystis (40 -42), and HeLa cells (16,43). The most successful of these studies identified up to 80 putative Trx targets (37).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we used the isotope-coded affinity tag approach to identify over 70 targets of Trx1 transnitrosylation and 50 targets of Trx1-mediated denitrosylation (43). Although a Trx mutant has been used to identify Trx targets in non-mammalian cells (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)44), its application in the identification of mammalian targets has been rare, presumably because of the presence of highly abundant cytosolic targets in the total cell lysates, such as Prx1, that compete for a limited number of binding sites on the Trx1 C35S mutant. This is the first report demonstrating that an nTrx1 C35S mutant can be used to identify novel Trx1 targets in the nucleus of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the disulfide proteomics have been led with higher plants: spinach (8,10,12), Arabidopsis (11,14), or cereal grains (12). A single study was led with cyanobacteria and revealed targets mostly different from those of higher plants (16).…”
mentioning
confidence: 99%
“…Subsequently, monocysteinic TRX mutants were used in affinity chromatography to trap interacting proteins (8)(9)(10)(11). Native TRX affinity columns also allowed retaining some targets by electrostatic interaction (12). Another technique was also developed that consists of a reduction of a crude soluble protein extract with reduced TRX followed by a separation of the proteins on a 2D gel after derivatization of the newly appeared thiols either with a fluorescent (13) or with a radioactive (14) reagent.…”
mentioning
confidence: 99%